PTU-073 Comparison Of Sicus Versus Mr-enterography In Patients With Crohn's Disease. (9th June 2014) - Alexakis, C; Chhaya, V; Tzias, D; Pilcher, J; Pollok, R
Abstract : Introduction: Small intestinal contrast-enhanced ultrasonography (SICUS) is an emerging radiological technique for the imaging of patients with Crohn's disease that avoids exposure to diagnostic medical radiation. We have previously demonstrated that SICUS is diagnostically comparable to small bowel barium follow through and computerised tomography in the diagnosis of Crohn's .1 MR enterography (MRE) is becoming the gold standard radiological technique for the diagnosis of complications in patients with Crohn's, but is expensive and access is limited. We aimed to compare the diagnostic sensitivity of SICUS with MRE in routine clinical practice. Methods: Patients with established Crohn's disease, who had undergone both SICUS and MRE within 6 months of each other were identified retrospectively from the radiology database at a UK tertiary centre. Imaging and reports were reviewed for both modalities. Kappa coefficient data was calculated for luminal parameters including the presence of strictures, stricture number and location, the presence of abscess/fistulae, mucosal thickening, active mucosal inflammation and fibrotic changes. Reported stricture lengths were compared using paired student's t- test. Inflammatory markers including platelet levels, where available, were recorded within 2 weeks of each of the imaging modalities as a surrogate marker for active inflammation. Results: 20 Crohn's patients were identified (10 male), with a mean age of 30.1 years at time of first investigation. Mean time between modalities was 72.3 days (range 2–147). There was no significant difference between mean platelet counts between the 2 radiological tests. Agreement between the 2 modalities was excellent for the presence of stricturing disease (k=0.92, 95% CI 0.71–1.00), stricture number (k=0.91, 95% CI 0.73–1.00) and stricture location (k=0.91, 95% CI 0.71–1.00). Agreement was good for the presence of fistulae (k=0.74, 95% CI 0.40–1.00) and mucosal thickening (k=0.74, 95% CI 0.40–1.00). Agreement was moderate for the presence of abscess (k=0.46 95% CI 0.14–1.00), acute mucosal inflammatory changes (k=0.55, 95% CI 0.19–0.90) and fibrotic changes (k=0.50, 95% CI 0.04–0.95). There was no significant difference in the mean estimated stricture length between MRE and SICUS. Conclusion: SICUS compares favourably with MRE in the diagnosis of complications in patients with Crohn's disease. This imaging technique is particularly useful in patients with stricturing (Montreal B2) disease. SICUS is a useful alternative diagnostic technique to MRE, particularly when access to MR may be limited or is poorly tolerated by the patient. Reference: Chatu S et al . Diagnostic accuracy of small intestine ultrasonography using an oral contrast agent in Crohn's disease: comparative study from the UK. Clin Radiol . 2012 Jun;67(6):553-9 Disclosure of Interest: None Declared.